IMPLEMENTASI KALMAN FILTER DALAM TEKNIK HAND TRACKING SEBAGAI KONTROL POINTER MOUSE KOMPUTER - Reswan, Yuza; Prabowo, Dedy Agung (Major of Information Systems Faculty of Computer Science Sriwijaya University, 2018)
In their daily life, humans usually use hands for the interaction between humans and machines or humans and human so that the human-computer interaction and computer-based Computer Vision using fingers has more value than using other objects. Many techniques are developed based on the Computer Vision model, one of the technique that is implemented in this field is Hand Tracking. The use of such techniques uses certain algorithms to improve performance, one of which is the filter algorithm.Kalman Filter is an estimator algorithm in which information from an object is detected in a frame and the status of the object in the previous frame to create an approximate status of the new state of the object so that the process of unstable object movements in the tracking process that occurs due to noise can be minimized by the kalman filter. The use of Hand Tracking techniques and Kalman Filter algorithm is expected to meet the needs of more advanced human and computer interactions. The results of this study are expected to be useful as a means of scientific development in the field of informatics engineering and the ability to build software in the field of Hand Tracking techniques and Kalman Filter algorithm as well as expected This application can be used for personal or public interest.